Pengaruh Penambahan Sodium Hipoklorit Dalam Analisa Amonia Air Secara Fenat - Haspiadi Haspiadi; Kurniawaty Kurniawaty; Fitriani Fitriani (Jurnal Riset Teknologi Industri, 2016)
The research has been conducted to study the effect of the addition sodium hypochlorite on the ammonia testing of water and waste water. This research was investigated the effect of excess of sodium hypochlorite  that added in to the sample has high turbidity. Sodium hypochlorite  solution to reduce turbidity was used at various volume: 25 mL, 30 mL, 35 mL, 40 mL, 45mL, 50 mL, 55 mL,60 mL.  The analysis   method according to SNI 06- 6989.30-2005, Methode of Amonia Testing with Spektrofotometer in water and waste water.The result of the experiment indicate   that sodium hypochlorite was added more than arranged in SNI 06-6989.30-2005  can effect  to the result of actual ammonia contain in the water semple.The maximum of sodium 'hypochlorite recommended to used in the sample high turbidity is 40 mL in 100 mL alkalin citrate solution.